Magnetic resonance imaging of vaginal support structure before and after Vecchietti procedure in women with Mayer–Rokitansky–Küster–Hauser syndrome. (22nd April 2018) - Huebner, Markus; DeLancey, John O.L.; Reisenauer, Christl; Brucker, Sara Y.; Preibsch, Heike; Fleischer, Sabrina; Schoeller, Dorit; Stefanescu, Diana; Rall, Katharina
Abstract: Introduction: It is unclear how pelvic floor supporting structures might be affected by the absence of the vagina. It was the aim of this prospective study to analyze the magnetic resonance imaging morphology of pelvic support prior and after a Vecchietti procedure in women suffering Mullerian agenesis (Mayer–Rokitansky–Küster–Hauser syndrome). Material and methods: 26 women with a diagnosis of Mayer–Rokitansky–Küster–Hauser syndrome associated vaginal agenesis were recruited prospectively prior to the laparoscopic creation of a neovagina according to the Vecchietti procedure. The primary outcome measure was the magnetic resonance imaging morphology of supporting structures. Secondary outcome measures were anatomical and functional vaginal length. Follow up was conducted six months after surgery. Results: Twenty‐six women were analyzed. Mean age was 19.8 ± 4.4 years (±SD) and mean body mass index was 23.7 ± 4.3 kg/m 2 (±SD). All were Caucasian. Supporting structures consistent with cardinal and uterosacral ligaments were visible on magnetic resonance imaging in all cases (100%). There were no levator ani defects. The vaginal apex could be visualized postoperatively in 12 women (46.2%) reaching up to Level I. The vagina was visible in both Level II and III with normal relations to the pelvic walls in all cases. On gynecological examination, vaginal length was 8.8 ± 2.1 cm (mean ± SD) anatomically and 10.2 ± 2.2 cm (mean ± SD) functionally. Conclusions: The preoperative presence of pelvic support structures into which the vagina is lengthened by the surgery likely explains the uncommon occurrence of vaginal prolapse in women who had the Vecchietti procedure.